LITERATURE REVIEW: IMPLEMENTATION OF HUMAN RESOURCE STRATEGY MANAGEMENT DEVELOPMENT IN THE COMPANY - Try Junanto (OIKONOMIA: Journal of Economics and Management Science, 2023)
The field of human resources is currently undergoing rapid changes and leads to a modern development system or can be said to be a human development model that aims to be able to overcome various types of problems that adhere to the direction of conflict disputes in the company and instead invites a definition that is more widespread than other perceptions so as to benefit the company and also to be able to develop its own development context. However, there are also some business fields that do not so much implement the use of human resources in their work, which adheres to the opposite context and more or less leads to other problem fields. Meanwhile, the context of the development field at this time can be said to have been fully implemented and used as a fortress of a company. This definition leads to various aspects or opinions from experts who corner the perception of the management field as the main center of development in the HR field. Therefore, the concept of review used in this research is based on a qualitative research approach which is an approach that is a description and is associated with research methods from several journals and several theories related to the development of the field of human resources, especially in the context of sustainable development and more able to bring towards a better and more developed. The results of this review point to the aspect of human resource development itself is in the aspect of functionalism and professionalism in the field of divisions within the company which is able to bring so much profit to employers